A dislexia na mídia impressa jornalística: análise de matérias publicadas nos jornais gazeta do povo e folha de S. Paulo (2005-2010) - Carvalho, Fernanda dos Santos (2013)
Positions about dyslexia and called disorders of reading and writing have been made and published in different spheres and social contexts , interfering in the different perspectives from which this issue is addressed in the designed and within the family , education and health . Interest in this study focus on the knowledge about dyslexia and so called disorders of reading and writing disseminated by national newspapers , in view of the important role that these media outlets play in shaping public opinion . The objective of this study is to analyze the articles published about dyslexia and disorders of reading and writing , between the years 2005 and 2010 , the newspaper Folha de S. Paulo and Gazeta do Povo . For the selection of newspapers , the criterion considered was the large number of runs. The materials are arranged from the following aspects : publication year , month , author , section in which it was published , the main theme and subthemes addressed line between the reader and the text published intended. Were analyzed quantitatively and qualitatively , 115 subjects . The themes discussed were problems reading and writing at school . Main subtopics are: appropriation of reading and writing , symptoms and diagnosis of dyslexia, case reports and stories of subjects diagnosed as dyslexic and interventions to address the problem . We observe that news stories tend to characterize dyslexia as a disease / problem due to factors organicists . This study highlights the need to implement research on the subject , in addition to enabling the interpretation of the ways print media highlights the issue at hand.